CELL MATERIAL INTERACTIONS AT THE NANO-BIO INTERFACE: IMPLICATIONS FOR REGENERATIVE MEDICINE - Ayesha Begum; Zahidul Islam; Shakib Ahmed (Yayasan Adra Karima Hubbi, 2026)
Cell-material interactions at the nano-bio interface play a pivotal role in the success of regenerative medicine, as these interactions dictate cell behavior, differentiation, and tissue integration. The advent of nanotechnology has enabled the development of materials with tunable properties at the nanoscale, providing new opportunities for enhancing tissue regeneration and healing. Despite the significant progress in this field, understanding the molecular mechanisms underlying these interactions remains a challenge. This study investigates the relationship between cells and nanomaterials, focusing on the impact of surface properties, topography, and chemical composition of materials on cellular behavior. The primary objective is to assess how engineered nanomaterials influence cellular responses such as adhesion, migration, proliferation, and differentiation. Experimental methods, including cell culture on nanostructured substrates, surface characterization using atomic force microscopy (AFM), and gene expression analysis, were employed to evaluate these interactions. The results demonstrate that nanomaterials with specific surface characteristics significantly enhance cell adhesion and proliferation, promoting tissue growth and regeneration. In conclusion, the nano-bio interface offers promising opportunities for developing advanced biomaterials for regenerative medicine, with implications for improving the functionality and biocompatibility of tissue-engineered constructs.